The Development of Problem-Based Learning Model E-Module Integrated with Multiculturalism in Elementary Schools - Desyandri, Desyandri; Agustina, Yana; Lusiana, Dewi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
The absence of technological teaching materials tailored to each local area's specific conditions served as the impetus for this research. The objective of this research is to generate e-modules that are both practical and valid as educational resources. This study employs the five stages of ADDIE development research: analysis, design, development, implementation, and evaluation. The research results indicate that the e-module developed by the researchers achieved a score of 89% for material expert validators, 86% for media expert validators, and 84% for language expert validators, all of which are classified as